Nasal decongestant and chronic headache: a case of naphazoline overuse headache? - Di Lorenzo, Cherubino (F1000Research, 2013)
Background: Chronic headache is an incapacitating condition afflicting patients at least for 15 days per month. In the most cases it is developed as a consequence of an excessive use of symptomatic drugs. Case: Here we report the case of a 34 year-old man suffering from chronic headache possibly related to the overuse of naphazoline nitrate nasal decongestant, used to treat a supposed chronic sinusitis. However, the patient did not suffer from sinusitis, but from a medication overuse headache (ICHD-II 8.3; ICD-10 44.41) that appeared to be due to excessive use of naphazoline. Conclusion: The use of naphazoline nitrate may result in an analgesic effect upon first use, through activation of adrenergic and opioidergic systems, followed by a pro-migraine effect via a late induction of an inflammatory cascade, modulated by nitric oxide and arachidonic acid. The observation that naphazoline detoxification relieved the patient’s headache, indicates that prolonged use of naphazoline may cause chronic headaches. Therefore, physicians should ask for details on the use of nasal decongestants in patients complaining of chronic headache, as they could potentially be suffering from a medication-overuse headache.